Economic and Statistical Analysis of Tourism in Uganda - World Bank Group (Washington, DC, 2013)
The Ministry of Tourism, Wildlife, and Antiquities (MTWA) instituted a sample survey of tourists exiting Uganda in 2012-the Tourism Expenditure and Motivation Survey (TEMS). This survey collected data on tourist expenditures, duration of stay, tourist activities, sites visited, levels of satisfaction, and suggestions for improvements in the sector. The purpose of this report is to present the results of the economic analysis of tourist expenditures, and the associated statistical analysis, to inform government decisions on how to increase the contribution that tourism makes to the growth of the Ugandan economy. The economic analysis of tourism based on the TEMS survey focuses on the impact of tourist expenditures on the economy. The scope is therefore limited to the impact of tourism exports, but these exports are important contributors to the development of the Ugandan economy, increasing foreign exchange earnings, and improving the balance of payments. The data show that leisure and cultural tourists spend 30 percent to 100 percent more than other types of tourists per visit to Uganda. This substantial difference in spending makes these tourists an attractive target in government efforts to increase the economic contribution of the tourism sector and reinforces the importance of strengthening the marketing of Ugandan tourism. The TEMS survey estimates that roughly 500,000 foreign tourists spent at least one night in Uganda in 2012, and nearly 75,000 of these were leisure or cultural tourists. In 2013 more than one million nonresidents visited Uganda, and it is estimated that about half of them of them stay at least one night. Tourists' overall satisfaction with their trip to Uganda is high. However, local transport in Uganda and insufficient visitor information are the most frequently cited sources of dissatisfaction and suggested areas for improvement.